3,3'-Diindolylmethane exhibits antileukemic activity in vitro and in vivo through a Akt-dependent process. - Ning Gao (Public Library of Science (PLoS), 2012)
3,3'-Diindolylmethane (DIM), one of the active products derived from Brassica plants, is a promising antitumor agent. The present study indicated that DIM significantly induced apoptosis in U937 human leukemia cells in dose- and time-dependent manners. These events were also noted in other human leukemia cells (Jurkat and HL-60) and primary human leukemia cells (AML) but not in normal bone marrow mononuclear cells. We also found that DIM-induced lethality is associated with caspases activation, myeloid cell leukemia-1 (Mcl-1) down-regulation, p21(cip1/waf1) up-regulation, and Akt inactivation accompanied by c-jun NH2-terminal kinase (JNK) activation. Enforced activation of Akt by a constitutively active Akt construct prevented DIM-mediated caspase activation, Mcl-1 down-regulation, JNK activation, and apoptosis. Conversely, DIM lethality was potentiated by the PI3K inhibitor LY294002. Interruption of the JNK pathway by pharmacologic or genetic approaches attenuated DIM-induced caspases activation, Mcl-1 down-regulation, and apoptosis. Lastly, DIM inhibits tumor growth of mouse U937 xenograft, which was related to induction of apoptosis and inactivation of Akt, as well as activation of JNK. Collectively, these findings suggest that DIM induces apoptosis in human leukemia cell lines and primary human leukemia cells, and exhibits antileukemic activity in vivo through Akt inactivation and JNK activation.